PET ROBOT - MOHAMED, FARALIZA (Universiti Teknologi PETRONAS, 2008)
The idea of the PET ROBOT is highly appropriate due to the r-apid changing technology in the modem world and the h\llllans changing ways of life. This teclmology could not only be the replacement for house pets but with detailed design and innovation it could be an assistant to humans at homes. Pet robot uses a microcontroller to control its functions. The micr{)controller will carry out instructions from the designed coding that is implemented to the microcontroller. Coding is designed and compiled using PIC Programming software. Different types of sensors are placed to the robot to give it intelligence. The pet robot will be not only be able to move forward, backward and tum but with the ability to 'see' by implementing sensol'S, the r{)bot is also able to avoid object obstacles along the way. Besides that, the robot can react to certain external input such as performing certain functions when it detects light and can react to sound. The project work requires both mechanical field for movement and electrical field for contr{)lling the r{)bot.